Enhancing Critical Thinking Skills in ChatGPT-Human Interaction: A Scoping Review - Lilia Raitskaya; Elena Tikhonova (Journal of Language and Education)
Introduction: The rapid integration of generative artificial intelligence (GenAI) technologies, including ChatGPT, into educational environments has introduced both opportunities and challenges for learners and educators. While GenAI can support advanced learning practices, it also raises concerns about critical engagement and the accuracy of generated content. Previous systematic reviews have explored GenAI’s relationship with critical thinking (CT) and self-regulated learning, but a focused synthesis of recent empirical evidence on GenAI’s impact on university students’ CT skills remains lacking.